Improving Multiliteracy Ability in the Integration of Islamic and Science Learning - Tukiyo Tukiyo; Purwo Haryono; Syamsul Arifin; Ari Kartiko; Fahlulia Rahma Shofiana (AL-ISHLAH: Jurnal Pendidikan, 2022)
Multiliteracy ability is an important ability to be mastered in the Society 5.0 era where the challenges faced by humans are increasingly complex, especially in the world of education and relation to religious life. This ability can be formed and enhanced through meaningful learning activities, one of which is the integrated learning of religion and science that is planned, organized, and evaluated on an ongoing basis as implemented by the Supreme Court Darul Ulum Rejoso Jombang. Because the integration of religion and science is still rarely carried out, several questions arise, namely how to implement integrative learning of religion and science in improving students' multiliteracy skills and what factors influence it. The method used in this research is a qualitative method with the type of case study research. Data were collected utilizing observation, interviews, and documentation which were analyzed descriptively. The results of this study are: 1) Integrative learning of religion and science at MA Unggulan Darul Ulum is implemented in 3 stages, namely, planning (compilation, and maturation of the syllabus and lesson plans), implementation (discussion, lectures, and demonstrations), and evaluation (daily exams). , PTS, PAS, and TA) and is also accompanied by supporting activities to improve reading, writing, conveying ideas based on religious and scientific critical thinking, and using various technological tools. 2) influencing factors, namely teachers, students, educational policies, facilities infrastructure.